Effects of Liraglutide Combined with Low Fat Diet on Neural and Thermogenic Activities of 5' - AMPK in the Hypothalamus: Expectations - Al-Domi, Hayder; Khalil, Raida; Batarseh, Nour (Progress in Nutrition, 2022)
Background: Medical nutrition therapy is essential in managing and preventing diseases. Liraglutide is among glucagon-like peptide-1(GLP-1) agonists’ play a critical role in managing weight as they could modulate the effectiveness of 5’ AMP-activated protein kinase (5'-AMPK) in the hypothalamus. Additionally, the neural activity of 5'-AMPK is negatively affected by high-fat diets; and it remains unclear how low-fat diets combined with liraglutide could counteract this effect. Objectives: To investigate the effects of a high-fat diet on the neural and thermogenic activities of 5’ –AMPK in the hypothalamus and the possible effects of combining a low-fat diet with a liraglutide regimen on 5’ –AMPK activity in the hypothalamus. Methods: We searched the available literature for articles published in PubMed, Science Direct, and ClinicaTrials.gov between November/2020 and January /2021, published in 6 years, and we included controlled clinical trials. Findings: A total 108 out of 230 articles included in our search, and findings revealed that high-fat diets negatively influence liraglutide and 5'-AMPK in the hypothalamus. In contrast, a low-fat diet could reverse this negative influence if combined with a dose of 1.8-3 mg/kg of liraglutide for up to 16 weeks. Conclusion: 5'-AMPK stimulates energy production in peripheral tissues, improves metabolic status, and liraglutide controls food intake in the hypothalamus, but high-fat diets counteract previously mentioned effects of liraglutide and 5'-AMPK. We found no adequate studies that adequately examined the effect of a low-fat diet on liraglutide and 5'-AMPK; hence, our concern was reviewing and predicting the possible effect of low-fat diets.